ChemInform Abstract: Four New 7, 8‐Epoxycembranoids from a Chinese Soft Coral Lobophytum sp. Issue 25 (24th June 2014) - Zhao, Min; Li, Xiubao; Zhao, Feng; Cheng, Shimiao; Xiang, Zheng; Dong, Jianyong; Huang, Kexin; Yan, Pengcheng
Abstract isolation, structural elucidation and inhibitory effect on lipopolysaccharide (LPS)‐induced nitric oxide (NO) production in mouse peritoneal macrophages